Heavy metal behavior in "Washing-Calcination-Changing with Bottom Ash" system for recycling of four types of fly ashes. (May 2018) - Zhu, Fenfen; Xiong, Yiqun; Wang, Yingying; Wei, Xiang; Zhu, Xuemei; Yan, Fawei
Highlights: Heavy metal behavior during one MSWI fly ash pretreatment process has been evaluated. Most heavy metal become more stable after treatment except Cr. XANES spectra has been proceeded to identify lead chemical species in four kinds of fly ash. Abstract: The Washing-Calcination-Changing with Bottom Ash (WCCB) system, effective at reducing chloride, was proposed to treat fly ash (FA) from a municipal solid waste incinerator (MSWI) before recycling FA in cement kiln as raw material. This study analyzed the behavior of heavy metals in four types of FA during WCCB treatment via Tessier and X-ray absorption fine structure (XANES) method. One FA was from the bag filter of a typical MSWI in Beijing, China (CFA), and the other three were from Japan (RFA, CaFA, and NaFA). All the metals were reduced especially Pb, Cd, and Hg (38.4–82.4%, 21.8–34.7%, and 100%, respectively). Besides Cr almost all heavy metals were stabilized according to Tessier analysis. Cr should be given more attention in WCCB as the formation of exchangeable Cr in the final residue. XANES result indicated that PbCl2 could be the main species of Pb in FA, while CaFA contains some PbO. The treated FAs contain PbCO3 and PbO besides PbCl2 . The Tessier results of Ni, Pb, Cd, Cr, and Cu showed that NaFA was better at heavy metal stabilization than the other FA, so NaHCO3 is a more suitable neutralizer in WCCB.